A bloodless civil war: The polarization of the press and political parties around the Great War in Asturias (1914-1919) - Agudín Menéndez, José Luis (Hispania Nova, 2020)
The purpose of these pages is to attend the ideological impact of the First World War in Asturias. Taking advantage of a favorable historiographical tessitura in the proliferation of investigations on the Great War and the public opinion to the heat of the centenary, this article deals with a fact hardly worked in Asturian historiography. The documentary support is based on the reading of the provincial newspapers (El Carbayón in Oviedo, El Noroeste, El Comercio and El Pueblo Astur in Gijón or La Voz de Avilés) as well as, occasionally, national newspapers (El Correo Español, El Siglo Futuro or El Socialista in Madrid). It also draws on literary sources and the consultation of municipal Minutes Book. A feather flies the beginning of the war, the arrival of cultural missions, the reception of submarine warfare and the allied celebrations at the end of hostilities are described here.
Keywords: World War I; pro-allied and Germanophiles; press history; public opinion; Melquíades Álvarez; Asturias